Progressive hemiparesis (Mills syndrome) with aphasia in amyotrophic lateral sclerosis. - Bäumer, D; Butterworth, R; Menke, R; Talbot, K; Hofer, M; Turner, M (Lippincott Williams and Wilkins, 2014)
The onset of motor symptoms in amyotrophic lateral sclerosis (ALS) is strikingly focal. In three-quarters of cases, weakness emerges unilaterally in one limb, typically spreading contiguously over months to become bilateral.(1) An extremely rare clinical syndrome of upper motor neuron-predominant, progressive hemiparesis was first described by American neurologist Charles Karsner Mills (1845-1930).(2) More typical ALS shares a common histopathologic signature with frontotemporal dementia (FTD), consisting of ubiquitinated neuronal and glial inclusions containing the DNA and RNA binding protein, TDP-43. Cognitive impairment may be detected in at least one-third of ALS cases and involves mainly deficits in language, executive function, and fluency, with variable levels of behavioral impairments that all have overlap with the purer FTD syndromes. Frank FTD is seen in up to 15% of patients with ALS, in whom it typically occurs before or soon after the development of motor symptoms, and is associated with a more rapid disease progression.(3.)